Inspeção, mapeamento e análise de manifestações patológicas em obras de arte especiais - Greca, Juliana Medeiros (2012)
Transpose landforms was extremely important since Prehistory and still is in the current days. For doing so, viaducts are used in order to promote the connection, access and development of every type of regions. As consequence, it has arose the need of preserving these structures and also their functionality, searching for alternatives of better maintenance. In Curitiba, Paraná state capital, the viaducts are present mainly on the biggest avenues, for example, the connectors, which link the Cidade Industrial de Curitiba – CIC – to other places of the city. This research consists of a study and mapping of pathologies located in “Conectora 5” viaducts, which registered start is placed on Campina do Siqueira district and goes up to CIC. The development of this research occurred according to some methodological procedures, where the literature, inspections, results analysis and mapping development are found. During all this process, it was also developed, based on two well-known methods of evaluating viaducts, an inspection sheet whit focus on the elements of this study. Also, it has been elaborated whit the goal of increasing the detailing of the pathologies found on the structures. As the result, the study comes up with a classification of the viaducts according to the pathologies’ incidence obtained on the inspection sheets.